Anti-Inflammatory and Immunomodulatory Effects of Paeonia Lactiflora Pall., a Traditional Chinese Herbal Medicine - He, Dong-Yi; Dai, Sheng-Ming (Frontiers in Pharmacology, 2011)
In China, Korea and Japan, a decoction of the dried root without bark of Paeonia lactiflora Pall. has been used in the treatment of rheumatoid arthritis, systemic lupus erythematosus, hepatitis, dysmenorrhea, muscle cramping and spasms, and fever for more than 1200 years. A water/ethanol extract of the root is now known as total glucosides of paeony (TGP), which contains more than 15 components. Paeoniflorin is the most abundant ingredient and accounts for the pharmacological effects observed with TGP in both in vitro and in vivo studies. The analgesic effect of TGP was confirmed in various animal models of pain, which may be mediated partly by adenosine A1 receptor. The direct anti-inflammatory effects of TGP were observed in animal models of both acute and subacute inflammation, by inhibiting the production of prostaglandin E2, leukotrience B4, and nitric oxide, and by suppressing the increase of intracellular calcium ion concentration. TGP was also reported to have protective effects of cells against oxidative stress. In vitro, dual effects of TGP were noted on the proliferation of lymphocytes, differentiation of Th/Ts lymphocytes, and the production of pro-inflammatory cytokines and antibodies. In vivo, TGP inhibited the delayed-type hypersensitivity in immuno-activated mice, and enhanced the delayed-type hypersensitivity in immuno-suppressed mice. In adjuvant arthritis rats, paeoniflorin exerted immunosuppressive effects. The beneficial effects of TGP in treating rheumatoid arthritis were verified by randomized controlled trials. The adverse events of TGP were mainly gastrointestinal tract disturbances, mostly mild diarrhea.